A Comparative Analysis of Immediate and Delayed-immediate Breast Reconstruction after Postmastectomy Radiation Therapy - Christopher, Adrienne N.; Morris, Martin P.; Broach, Robyn B.; Serletti, Joseph M. (Journal of Reconstructive Microsurgery, 2021)
Background Postmastectomy radiation therapy (PMRT) is an important component in the treatment of locally advanced breast cancer. Optimal timing of therapy in relation to autologous breast reconstruction (ABR) remains clinically debated. Herein, we comparatively analyze short- and long-term outcomes between immediate ABR (I-ABR) and delayed-immediate ABR (DI-ABR) in the setting of PMRT.Methods Adult patients undergoing ABR with PMRT were separated into cohorts based on reconstructive timeline: I-ABR or DI-ABR. The groups were propensity matched 1:1 by age, body mass index, and comorbidities. Surgical site events and long-term clinical outcomes (readmissions, reoperations, and revision procedures) were collected. Univariate analyses were completed using Pearson's chi-squared tests and Fisher's exact tests, and statistical significance was set at p < 0.05.Results One hundred and thirty-two flaps (66 in each cohort) were identified for inclusion. Patients with I-ABR were more likely to experience fat necrosis (p = 0.034) and skin necrosis (p < 0.001), require additional office visits (p < 0.001) and outpatient surgeries (p = 0.015) to manage complications, and undergo revision surgery after reconstruction (p < 0.001). DI-ABR patients, however, had a 42.4% incidence of complications following tissue expander placement prior to reconstruction, with 16.7% of patients requiring reoperation during this time. Only one patient (I-ABR) experienced flap loss due to a vascular complication.Conclusion The complications encountered in both of these groups were not prohibitive to offering either treatment. Patients should be made aware of the specific and unique risks of these reconstruction timelines and involved throughout the entire decision-making process. Plastic surgeons should continue to strive to elucidate innovative approaches that facilitate enhanced quality of life without compromising oncologic therapy.
Keywords: postmastectomy radiation therapy; tissue expanders; delayed-immediate autologous breast reconstruction; immediate autologous breast reconstruction